Prediction-based energy efficient opportunistic routing protocol in wireless sensor networks. (8th May 2020) - Nagadivya, S.; Manoharan, R.
Opportunistic routing is a most promising routing method for improving the network lifetime and throughput of wireless sensor networks (WSN). It utilises the broadcast nature of WSN, that allows to select and prioritise a node from the potential forwarder set as next-hop forwarder. The design of energy efficient routing protocol becomes one of the major concern in WSN, due to limited battery power of a sensor node. The common energy loss reasons of existing routing protocols are: 1) packets may travel through a specific set of sensor nodes will drain out a battery energy very soon; 2) packets discard will create a packet retransmission. Opportunistic routing broadcast nature will avoid packet retransmission. The proposed energy efficient Markov prediction-based opportunistic routing (EEMPOR) protocol uses the following metrics to select and prioritise the energy efficient nodes namely, number of transactions of a node and residual energy of a node. Then proposed protocol shows that Markov prediction-based opportunistic routing protocol provides better network performance than non-prediction-based method. Simulation results show, that the proposed protocol outperforms the existing OR in terms of consumed energy, residual energy, network lifetime, and throughput.